Children's Sleep During COVID-19: How Sleep Influences Surviving and Thriving in Families. (2nd September 2021) - MacKenzie, Nicole E; Keys, Elizabeth; Hall, Wendy A; Gruber, Reut; Smith, Isabel M; Constantin, Evelyn; Godbout, Roger; Stremler, Robyn; Reid, Graham J; Hanlon-Dearman, Ana; Brown, Cary A; Shea, Sarah; et al.
Abstract: Objective: The COVID-19 pandemic has the potential to disrupt the lives of families and may have implications for children with existing sleep problems. As such, we aimed to: (1) characterize sleep changes during the COVID-19 pandemic in children who had previously been identified as having sleep problems, (2) identify factors contributing to sleep changes due to COVID-19 safety measures, and (3) understand parents' and children's needs to support sleep during the pandemic. Methods: Eighty-five Canadian parents with children aged 4–14 years participated in this explanatory sequential, mixed-methods study using an online survey of children's and parents' sleep, with a subset of 16 parents, selected based on changes in their children's sleep, participating in semi-structured interviews. Families had previously participated in the Better Nights, Better Days (BNBD) randomized controlled trial. Results: While some parents perceived their child's sleep quality improved during the COVID-19 pandemic (14.1%, n = 12), many parents perceived their child's sleep had worsened (40.0%, n = 34). Parents attributed children's worsened sleep to increased screen time, anxiety, and decreased exercise. Findings from semi-structured interviews highlighted the effect of disrupted routines on sleep and stress, and that stress reciprocally influenced children's and parents' sleep. Conclusions: The sleep of many Canadian children was affected by the first wave of the COVID-19 pandemic, with the disruption of routines influencing children's sleep. eHealth interventions, such as BNBD with modifications that address the COVID-19 context, could help families address these challenges.